2014
DOI: 10.1111/febs.12934
|View full text |Cite
|
Sign up to set email alerts
|

Developing predictive rules for coordination geometry from visible circular dichroism of copper(II) and nickel(II) ions in histidine and amide main‐chain complexes

Abstract: Circular dichroism (CD) spectroscopy in the visible region (vis‐CD) is a powerful technique to study metal–protein interactions. It can resolve individual d–d electronic transitions as separate bands and is particularly sensitive to the chiral environment of the transition metals. Modern quantum chemical methods enable CD spectra calculations from which, along with direct comparison with the experimental CD data, the conformations and the stereochemistry of the metal–protein complexes can be assigned. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 40 publications
4
32
0
Order By: Relevance
“…4B that the visible CD spectra are very similar. There are some minor differences in the relative intensity of the positive and negative CD bands, but in comparison to the wavelength shifts seen between HSA and its N-terminal peptide models, these are not significant enough to suggest a different binding conformation (58).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…4B that the visible CD spectra are very similar. There are some minor differences in the relative intensity of the positive and negative CD bands, but in comparison to the wavelength shifts seen between HSA and its N-terminal peptide models, these are not significant enough to suggest a different binding conformation (58).…”
Section: Resultsmentioning
confidence: 80%
“…Visible CD spectra are extremely sensitive to coordination; the intensity and even sign of the CD bands will be greatly influenced by even small changes in geometry (57,58). Cu 2ϩ crosslinking between two adjacent A␤ molecules is not supported by the data.…”
Section: Discussionmentioning
confidence: 96%
“…Such a band pattern is characteristic for square planar complexes of peptides containing the N-terminal R1a-R2a-His sequence (so-called ATCUN or NTS motif), shown in Fig. 13A [ [94][95][96][97]. By looking at the original peptide sequence, we stated that this effect could only be explained by a cleavage of either of two peptide bonds flanking the Glu residue.…”
Section: Peptide Bond Hydrolysis In Four-coordinate Square-planar Commentioning
confidence: 95%
“…To identify the histidine residues that participate in nickel ion binding and further influence TLR4 interactions and IL-8 production, we assessed the nickel ion binding abilities of histidine mutants via CD spectroscopy, measuring ellipticity at 440 nm and 538 nm that represented the d-d transition when formation of nickel-protein complex3132333435. WT protein reaction with the metal chelating agent, EDTA, was used as the reference.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the nickel ion preferentially adopts planar coordination geometry31323335. The nickel ion has coordination numbers by four ligands34. It is reported that histidine, aspartate, glutamate and cysteine are the typically residues to coordinate nickel, among which, histidine is the most frequent over other amino acids59.…”
Section: Discussionmentioning
confidence: 99%